Distribution of metastases after radiotherapy in relation to radiation exposure fields: evaluation by 18F-FDG PET/CT - Jiucen Liang; Wei Li; Rusen Zhang; Wen Li; Peiyin Lin; Hao Nie (Scientific Reports, 2024)
Abstract To evaluate the distribution of metastases after radiotherapy using 18F-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography (18F-FDG PET/CT). 67 patients with 501 new metastases revealed by 18F-FDG PET/CT after radiotherapy were included in this retrospective study. The metastases were divided into radiation area (RA) and non-radiation area (NRA), based on their locations inside or outside the radiation exposure field. Patients were divided into two groups based on the comparison of lesions number between RA and NRA: group A (NRA ≤ RA) and group B(NRA > RA). The distribution characteristics of metastases and their relationship with clinical data were analyzed. 67 patients were included in the study. A total of 501 lesions were detected: 122 in RA and 379 in NRA. 28 patients resulted in group A and 39 in group B. Patients with lesion number (LN) ≤ 5 were primarily assigned to Group A (56.1%, 23/41), whereas those with LN > 5 were primarily assigned to Group B (80.8%, 21/26). A statistically significant difference in lesion count was observed between the two groups (χ2 = 8.809, P = 0.003).Among 19 patients with RA = 0, 17 had LN ≤ 5 and 2 had LN > 5. In contrast, among 25 patients with NRA = 0, 10 had LN ≤ 5 and 15 had LN > 5. A significant difference was noted between patients with RA = 0 and those with NRA = 0 (χ2 = 4.728, P = 0.030). An notable characteristic in the distribution of metastases following radiotherapy is their tendency to occur outside the irradiation area. This indicated that the radiotherapy exposure area acquires a certain tumor growth inhibitory effect, potentially lasting over time. Based on these observations, there may be potential for developing novel preventive irradiation techniques.